COMPARISON OF LEVEL OF FITNESS CARDIOPULMONARY WOMEN IN DIFFERENT AGE GROUPS (Fiep Bulletin - online, 2013)
Along the years the aging process has  been followed  by a progressive loss of the individual's physiological capacity. There is also at this stage the cardiorespiratory endurance that undergoes changes according to aging, thus decreasing the amount of oxygen  that an individual is able to capture and transport into the body tissues. By evaluating women, this paperwork aimed at making a comparison between different ages and checking what happens with the cardiorespiratory endurance in the aging process. The subjects of the research were women ranging from 30 to 69 years of age. PAR – Q and IPAQ questionnaires were used and they identified the level of physical activity practiced by the sample.  The women had their weights and heights evaluated, the body mass index calculated, which pointed out a potential overweight, measuring of the fat percentage that are triceps, abnominal and iliacus muscles, as well as Cooper tests applied to evaluate the cardiorespiratory endurance of the sample, descriptive statistical and variance tests were taken with post-hoc analysis of TUKEY, with a significance level stipulated in 0,05. It was observed that in  antropometric variables the groups did not differ including the BMI (Body Mass Index). As for the percentage of fat it was noted that group 3, with higher ages, showed higher amounts than the others. Concerning cardiorespiratory endurance, the younger group (G1) showed higher values that the others, and group 3 (G3) had the worst result in the COOPER test,.
Keywords: Cardiorespiratory; physiological capacity; aging